Accuracy and Safety of Percutaneous Lumbosacral Pedicle Screw Placement Using Dual-Planar Intraoperative Fluoroscopy - Dunn, Conor (Asian Spine J, 2018)
STUDY DESIGN: Retrospective case series with prospective arm. PURPOSE: To assess the safety and accuracy of percutaneous lumbosacral pedicle screw placement (PLPSP) in the lumbosacral spine using intraoperative dual-planar fluoroscopy (DPF). OVERVIEW OF LITERATURE: There are several techniques available for achieving consistent, safe, and accurate results with PLPSP. There is a paucity of literature describing the beneficial operative, economic, and clinical outcomes of DPF, the most readily accessible image guidance system. METHODS: From 2004 to 2014, 451 consecutive patients underwent PLPSP using DPF, for a total of 2,345 screw placement. The results of prospectively obtained postoperative computed tomography (CT) examinations of an additional 41 consecutive patients were compared with the results of 104 CT examinations obtained postoperatively due to clinical symptomatology; these results were interpreted by three reviewers. The rates of revision indicated by misplaced screws with consistent clinical symptomatology were compared between groups. Pedicle screw placement was graded according to 2-mm increments in medial pedicle wall breach and measurement of screw axis placement. RESULTS: Seven of the 2,345 pedicle screws placed percutaneously with the use of the dual-planar fluoroscopic technique required revision because of a symptomatic misplaced screw, for a screw revision rate of 0.3%. There were no statistically significant demographic differences between patients who had screws revised and those who did not. All screws registered greater than 10 mA on electromyographic stimulation. In the 41 prospectively obtained CT examinations, one out of 141 screws (0.7%) was revised due to pedicle wall breach; whereas among the 104 patients with 352 screws, three screws were revised (0.9%). CONCLUSIONS: DPF is an extremely accurate, safe, and reproducible technique for placement of percutaneous pedicle screws and is a readily available and cost-effective alternative to CT-guided pedicle screw placement techniques. Postoperative CT evaluation is not necessary with PLPSP unless the patient is symptomatic. Acceptable electromyographic thresholds may need to be reevaluated.